2004
DOI: 10.1007/s00702-004-0119-x
|View full text |Cite
|
Sign up to set email alerts
|

Roles for gliotransmission in the nervous system

Abstract: Astrocytes were long referred to as passive cells in the central nervous system (CNS). However, the application of fluorescent Ca2+ indicators revealed their "Ca2+ excitability" in response to a variety of stimuli. Since then, evidence showing that astrocytes release chemical transmitters and can modulate synapses has led to a new integrative view of the astrocyte. While it is inarguable that astrocytes play essential roles in nervous system function, and that gliotransmission modulates synapses, a significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
0
2

Year Published

2004
2004
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(42 citation statements)
references
References 30 publications
1
39
0
2
Order By: Relevance
“…Cytoplasmic calcium is a trigger for "gliotransmission" (Araque et al, 1999;Zhang and Haydon, 2005;Verkhratsky et al, 2012). ATP and/or glutamate are commonly released from astrocytes by gliotransmission.…”
Section: Discussionmentioning
confidence: 99%
“…Cytoplasmic calcium is a trigger for "gliotransmission" (Araque et al, 1999;Zhang and Haydon, 2005;Verkhratsky et al, 2012). ATP and/or glutamate are commonly released from astrocytes by gliotransmission.…”
Section: Discussionmentioning
confidence: 99%
“…3) , indicating that the function of demonstrated alterations in astrocytic processes in response to EC is related to enhancing synaptic function. Clearly there is an experience-dependent enhancement of astrocytic-synaptic communication, an important finding in light of the fact that perisynaptic astrocytes modulate synaptic transmission in response to synaptically released neurotransmitters, and themselves release neurotransmitter (Oliet et al, 2001;Zhang and Haydon, 2005). Additionally, astrocytes are involved in GABA and glutamate re-uptake and metabolism (Schousboe et al, 1992;Bezzi et al, 1999) and can conduct excitation via propagated Ca 2+ waves which can directly influence neuronal activity (reviewed by Zhang and Haydon, 2005).…”
Section: Astrocytesmentioning
confidence: 99%
“…Clearly there is an experience-dependent enhancement of astrocytic-synaptic communication, an important finding in light of the fact that perisynaptic astrocytes modulate synaptic transmission in response to synaptically released neurotransmitters, and themselves release neurotransmitter (Oliet et al, 2001;Zhang and Haydon, 2005). Additionally, astrocytes are involved in GABA and glutamate re-uptake and metabolism (Schousboe et al, 1992;Bezzi et al, 1999) and can conduct excitation via propagated Ca 2+ waves which can directly influence neuronal activity (reviewed by Zhang and Haydon, 2005). In CA1 of the hippocampus, where nearly 60% of the synapses are contacted directly by astrocytic processes (Ventura and Harris, 1999), postsynaptic glutamate receptors are activated by glutamate spillover from neighboring terminals (in addition to glutamate released from the presynaptic terminal) (see Kullmann et al, 1999).…”
Section: Astrocytesmentioning
confidence: 99%
“…Later studies demonstrated that this process can be observed in acute brain slices[71,72,73,74,75,76,77,78,79] and in vivo [80]. Astrocytes were later shown to release a number of chemical transmitters, including ATP[81,82,83,84,85], D-serine[86,87,88,89], TNF-alpha[90,91], and ANP[92], in a process that has recently been termed gliotransmission[93]. Based on the early studies of gliotransmission, the concept of the tripartite synapse was proposed[94], highlighting the role of the astrocyte as a third active element in information processing at the synapse[95,96,97,98,99].…”
Section: Astrocytes As Neuromodulatorsmentioning
confidence: 99%